2012
DOI: 10.2741/495
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Chagas disease: time to move on

Abstract: Trypanosoma cruzi is the etiologic agent of Chagas disease. The contributions of parasite and immune system for disease pathogenesis remain unresolved and controversial. The possibility that Chagas disease was an autoimmune progression triggered by T. cruzi infection led some to question the benefit of treating chronically T. cruzi-infected persons with drugs. Furthermore, it provided the rationale for not investing in research aimed at a vaccine which might carry a risk of inducing autoimmunity or exacerbatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 144 publications
1
35
0
4
Order By: Relevance
“…There are some questions that remain to be explained such as whether the autoantibody and autoreactive T-cell responses are pathogenic and whether any pathogenic responses can be maintained in the absence of infection. It is also unclear why the presence of mononuclear cells in the heart causes damage and their connection with release of auto-antigens and production of autoantibodies to the heart and whether they can be preserved in the nonattendance of infection [66,99]. The autoimmune theory of Chagas disease continues to be confronted because an antiself mechanism that triggers inflammatory effectors has not been identified [100,101].…”
Section: Pathology and Pathogenesismentioning
confidence: 96%
See 1 more Smart Citation
“…There are some questions that remain to be explained such as whether the autoantibody and autoreactive T-cell responses are pathogenic and whether any pathogenic responses can be maintained in the absence of infection. It is also unclear why the presence of mononuclear cells in the heart causes damage and their connection with release of auto-antigens and production of autoantibodies to the heart and whether they can be preserved in the nonattendance of infection [66,99]. The autoimmune theory of Chagas disease continues to be confronted because an antiself mechanism that triggers inflammatory effectors has not been identified [100,101].…”
Section: Pathology and Pathogenesismentioning
confidence: 96%
“…Production of IL-10 and TGF-b negatively regulates nitric oxide production [61,66] and these downregulatory cytokines appear to be related to parasite replication by inhibition of macrophage trypanocidal activity [17, 67,68]. Neutralization of endogenous IL-10 conducts an increase in T. cruzi induced IFN-g production and parasite killing [67,69].…”
Section: Pathology and Pathogenesismentioning
confidence: 99%
“…At a minimum, there is a poor correlation between the degree of cardiac dysfunction and parasite burden found on histopathologic evaluation that suggests more to the story than simple parasite persistence. 29,30 On the other hand, antibodies have been identified in Chagas disease that target beta-adrenergic receptors, but despite a biologically plausible association with autonomic dysfunction, these have not been shown to be associated with either the extent of cardiac disease nor unique to Chagasic cardiomyopathy. 30,31 One major aspect of this debate is its implication for treatment decisions, since an autoimmune pathophysiology would minimize the role for specific antiparasitic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 On the other hand, antibodies have been identified in Chagas disease that target beta-adrenergic receptors, but despite a biologically plausible association with autonomic dysfunction, these have not been shown to be associated with either the extent of cardiac disease nor unique to Chagasic cardiomyopathy. 30,31 One major aspect of this debate is its implication for treatment decisions, since an autoimmune pathophysiology would minimize the role for specific antiparasitic therapy. This discussion has recently grown more significance in light of the BENEFIT trial published last year, which confirmed that benznidazole treatment reduced parasite detection by polymerase chain reaction, but found no difference in cardiac events after treatment of cardiac Chagas disease patients with mild heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several challenges have impaired the development of therapeutic strategies, and much remains unknown about vector-host interactions and the mechanisms behind the various pathological symptoms associated with the disease. Only recently has it been determined that the chronic stages of the disease are associated with parasite persistence and that autoimmune mechanisms may not be responsible for organ damage, as hypothesized for several decades previously (25). Since the presence of parasites is critical for the disease, it is necessary to decipher the cascade of events that occur following infection, increasing our understanding and the potential to create drugs that can effectively treat the disease.…”
Section: Discussionmentioning
confidence: 99%